Ideal L2 Pre-service Teacher Selves: The Case of University Pre-service Teachers in Costa Rica - Murillo Miranda, Carlos (2024)
The ‘L2 Motivational Self System’ (L2MSS) (Dörnyei & Ryan, 2015) sheds light on theoretical tenets for research in language learner motivation. The L2MSS has been adapted into the ‘Possible Language Teacher Self’ (PLTS) (Kubanyiova, 2009) to explore language teacher motivation. Nonetheless, there is scarce research on a self-system for L2 pre-service teachers. Therefore, in this qualitative study, the characteristics of the Ideal L2 Pre-Service Teacher Self were explored to identify a possible motivational self-system. In-depth semi structured interviews were conducted and thematic analysis was implemented. Participants (N=2) were pre service L2 teachers from a university in Costa Rica. Findings revealed that participants mentioned four common traits of an ideal L2 pre-service teacher self: (1) passion, (2) knowledge, (3) adaptability, and (4) language proficiency. Contrary to Kubanyiova’s (2009) PLTS and Dörnyei’s (2009b) and Dörnyei & Ryan’s (2015) L2MSS, both participants share an ‘L2 Pre-service Teacher Self System’ including four elements: (1) Ideal L2 Pre-service Teacher Self, (2) ought-to L2 Pre-service Teacher Self, (3) current L2 Pre-service Teacher Self, and (4) Feared L2 Teacher Self. It is discussed and concluded that a PLTS system might include the elements just mentioned. However, further exploration on an L2 Pre-Service Teacher Self is mandatory to better understand the motivation and self-identity of L2 pre-service teachers.